PRIMARY CORRECTION OF THE NASAL DEFORMITY ON PATIENTS WITH UNILATERAL CLEFT LIP - Silvia RAILEAN; Cristina POȘTARU; Roman LUPAN; Odi NABILA (Buletinul Academiei de Ştiinţe a Moldovei: Ştiinţe Medicale, 2022)
Introduction. Orofacial clefts, is a group of conditions that includes cleft lip, cleft palate, and both together. Symmetry of the face can be obtained with primary nose reconstruction. The goal: Analysis of patients with unilateral complete cleft lip patients treated with or without a primary nasal correction at the time of cleft lip repair were compared to evaluate the relevance of early surgical correction of the nose Material and method. The 5 unilateral cleft subjects were operated on in 2022 by a technique of primary cleft nose correction (PCR), and 5 were operated without primary nose reconstruction (NNC). The anteroposterior and inferior facial appearances of each of the cases have been evaluated. A computer-based method of measuring nasal asymmetry was used to objectively analyze the results and compare them between children with and without primary nasal reconstruction. Measuring was done before and after the surgery and include qualitative and quantitative measurements. Results: The results support the observation that nasal shape become symmetric in children that support primary nasal reconstruction and asymmetric in children without primary nasal reconstruction. Conclusion: Primary nose reconstruction result in better cosmetic outcomes.